Metaniche session 2016: Tailor-made sensors for rapid Therapeutic Drug Monitoring –Interactions between Biomaterial Physicists, Chemical Engineers and Clinicians for successful translation of technologies in Healthcare - Yoshimi Y; Pushkala S; Vijaykumar H; Dedeepiya VD; Ignacy A; Swaminathan J; Rajmohan M; Karthick R; Abraham SJ (Journal of Stem Cells and Regenerative Medicine, 2016)
The Metaniche session is an academic session conducted as a part of Nichi-In Centre for Regenerative Medicine (NCRM)’s novel Initiatives' Conclave in Healthcare Every year (NICHE), the ‘NCRM NICHE’ organized every year in the month of October by Nichi-In Centre for Regenerative Medicine (NCRM), an Indo-Japan academic Institute based at Chennai, India. The Metaniche session aims to bring together the realms of Physics, Chemistry and Biology by portraying inventions or discoveries in physical and chemical sciences which are in the pipeline with high application potential in biology and healthcare. The Metaniche session-2016, held on 22nd October, 2016 in Chennai, India was on the application of biomaterial-based sensors for application in rapid therapeutic drug monitoring (TDM) systems. The session focussed on the role of biomaterials in medicine giving an overview and history of the evolution of biomaterials to suit the growing needs in medicine, followed by emphasizing the need for rapid TDM systems. The final part portrayed the development of tailor-made sensors for rapid TDM using molecularly imprinted polymers as given below.